Evaluasi User Interface Aplikasi Kitabisa Menggunakan Metode Heuristic Evaluation - Yohana Tri Utami; Evania Intiha (Jurnal Komputasi, 2022)
The public is made aware of a cause via a gift or fundraising event, enabling many people to do good. This study seeks to assess how comfortable users are using the Kitabisa application and to pinpoint any problems so that interface design mockup can be developed as potential fixes. The comfort felt by application users can be used as a determinant that the application can be categorized as a good application. The discovery of problems felt by Kitabisa users included inconsistencies in language, appearance, colors, and icons causing users to feel confused when using the Kitabisa Application.The Heuristic Evaluation is a method that involves user interface experts who are expert with the aim of finding user interface problems. The Heuristic Evaluation method will be used to guide the flow or steps that will be carried out in each process during the analysis and evaluation of the Kitabisa application so the solution can be madeÂ  for the problems found. Interface usability testing was carried out by finding problems in the Kitabisa application interface design and this test was successfully carried out through usability testing in order to collect feedback in the form of comments from evaluators and make improvements to the Kitabisa application mockup design interface based on comments from experts.